Pengaruh Media Komik terhadap Kemampuan Menulis Cerpen Siswa Kelas XI SMA Negeri 1 Cijaku - Hayanah, Siti; Arafat, Yasser (Universitas Mathla'ul Anwar Banten, 2024)
This study aims to examine the influence of comic media on the writing ability of short stories of Grade XI students at SMA Negeri 1 Cijaku in the academic year 2024/2025. The ability to write short stories is an important aspect in the Indonesian language learning process aimed at developing students' creativity, imagination, and language skills. However, students often face difficulties in writing short stories, especially in generating story ideas, developing plots, and using language effectively. This research uses an experimental method with a Control Group Pre-Test Post-Test Design. The research population consists of all Grade XI students at SMA Negeri 1 Cijaku, totaling 123 students. The sampling technique used Random Sampling, resulting in Grade XI-1 being selected as the experimental group and Grade XI-4 as the control group, each with 30 students. The experimental group received short story writing lessons using comic media, while the control group used series of pictures as media. Data was collected through pre-test and post-test of short story writing ability. Data analysis used independent t-test to observe significant differences between the two groups. The results of the analysis indicate a positive and significant influence of using comic media on the writing ability of short stories of Grade XI students at SMA Negeri 1 Cijaku. The average post-test score of the experimental group using comic media (78.36) was higher compared to the control group using picture series media (64.46), with a calculated t-value of 8.620 and a critical t-value of 1.684 at a significance level of α = 0.05. The calculated t-value is greater than the critical t-value, therefore based on the hypothesis testing criteria, H0 is rejected and H1 is accepted. This indicates that comic media is more effective in enhancing the writing ability of short stories of students compared to picture series media. This research has important implications for Indonesian language teachers in selecting appropriate learning media to enhance students' short story writing abilities. Comic media can be an effective alternative to increase students' motivation, interest, and writing skills. Furthermore, this research also provides recommendations for schools to provide innovative and engaging learning media for students, making the learning process more effective and enjoyable.